2012
DOI: 10.1111/j.1600-0722.2011.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relative efficacy of cognitive and non‐cognitive factors as predictors of dental anxiety

Abstract: Although previous research has successfully tested the usefulness of cognitive and non-cognitive factors to predict dental anxiety, they have rarely been jointly analysed. This study therefore aimed to compare the relative predictive power of a set of cognitive and non-cognitive factors in accounting for dental anxiety scores. A sample of 167 Spanish undergraduate students (81.4% women; mean age 21.2 yr) completed a questionnaire comprising measures of dental anxiety, non-cognitive antecedents of dental anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
25
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 37 publications
9
25
1
1
Order By: Relevance
“…In particular, perceptions of the dental experience as being uncontrollable, unpredictable, dangerous, and disgusting are believed to be crucial in the determination of dental anxiety and fear. Consistent with this theory, a number of studies have now supported the role of cognitive perceptions as being mediating factors between aversive experiences and dental anxiety and fear . However, the assessment of aversive dental experiences in this study is still rather rudimentary.…”
Section: Discussioncontrasting
confidence: 99%
“…In particular, perceptions of the dental experience as being uncontrollable, unpredictable, dangerous, and disgusting are believed to be crucial in the determination of dental anxiety and fear. Consistent with this theory, a number of studies have now supported the role of cognitive perceptions as being mediating factors between aversive experiences and dental anxiety and fear . However, the assessment of aversive dental experiences in this study is still rather rudimentary.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with this, our study found that cognitive vulnerability and dental expectancies significantly predicted children's dental fear, after controlling for the effects of negative dental experiences. These results support the relevance of cognitive elements in explaining dental fear in the child population, as previous findings from child and adult research have already identified.…”
Section: Discussionsupporting
confidence: 90%
“…Cronbach's α reliability for this scale was 0.76. Previous versions of this scale have been found to have strong associations with dental fear . As presented below, the scale used in this study was also positively correlated with dental fear.…”
Section: Methodssupporting
confidence: 55%